Human Governance in State Islamic Religious Council - Dato' Hasnah Hj Haron; Zubaidah Zainal Abidin; Nathasa Mazna Ramli; Avylin Roziana Mohd Ariffin; Nurul Nazlia Jamil; Kasumalinda Alwi (Faculty of Industrial Management, Universiti Malaysia Pahang, 2024)
VOL.6, ISSUE1 (Page : 441–454)